Risk Factors for the Incident of Type 2 Diabetes Mellitus in the 20-44 Years Age Group in the Working Area of the Ulee Kareng Health Center in 2023 - Jihan Soraya Hermawan; Agustina Agustina; Anwar Arbi (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: The increase in the incidence of type 2 diabetes mellitus indicates that many individuals are unaware of the urgency of this disease, especially in the working area of Puskesmas Ulee Kareng, which has the highest prevalence. Objective: The study aims to identify the risk factors for the occurrence of type 2 diabetes mellitus in the age group of 20-44 years in the working area of Puskesmas Ulee Kareng in 2023. Method: The research design is descriptive-analytical with a case-control approach in a 1:1 comparison. The study population consists of all patients aged 20-44 years at Puskesmas Ulee Kareng, totaling 162 individuals. Sampling was conducted using convenience sampling, and the sample size was determined using the Lameshow formula, resulting in 47 diabetes patients as cases and 47 non-diabetic samples as controls. Data were collected from December 19, 2023, to January 2, 2024, using questionnaires and secondary data. Data analysis was performed using Chi-Square tests and Odds Ratio (OR) calculations with SPSS software. Result: The univariate analysis results indicate that respondents' knowledge about diabetes mellitus is low (42.6%), heavy physical activity (26.6%), poor dietary patterns (59.6%), hypertension (67.0%), and a family history of type 2 diabetes (50%). The bivariate analysis shows a significant relationship between knowledge (p=0.014; OR=3.157), physical activity (p=0.021; OR=14.103), dietary patterns (p=0.006; OR=3.348), hypertension (p=0.000; OR=36.667), and family history (p=0.015; OR=3.419) with the incidence of type 2 diabetes mellitus. Conclusion: In conclusion, knowledge, dietary patterns, physical activity, hypertension, and family history are risk factors for type 2 diabetes mellitus. It is recommended that Puskesmas prioritize community education on healthy lifestyles, increase physical activity, improve dietary habits, and conduct regular health monitoring.